Kontribusi Fintech Pada Inklusi Keuangan Di Negara Pasar Berkembang-Sebuah Meta Analysis - Sibarani, Bintang B.; Prihatni, Rida; Gurendrawati, Etty (Feb Universitas Dirgantara Marsekal Suryadarma, 2025)
The contribution of this meta analysis study is to explore the role of fintech innovations on financial inclusion in emerging markets such as Africa, India, Turkey, and the ASEAN region, in expanding financial access, improving literacy, and supporting the achievement of greater financial inclusion through a meta-analysis. In emerging markets, financial inclusion remains a major challenge due to limited banking infrastructure, low financial literacy, and geographic barriers, especially in rural areas. In countries such as Indonesia, India, Nigeria, Bangladesh, Brazil, and Kenya, a large portion of the adult population still does not have access to formal financial services. Reliance on the informal financial system remains high, and access to digital services is hampered by limited internet connectivity in remote areas. Fintech has revolutionized access to financial services in emerging markets, especially for populations that do not have access to traditional banking. Technologies such as mobile banking, digital payments, peer-to-peer lending, and blockchain help overcome geographic and socio-economic barriers, thereby increasing financial inclusion. For example, M-Pesa in Kenya, Ovo and GoPay in Indonesia, and Paytm in India have expanded access to financial services for millions of users.